A study on creating awareness of Malay ethnic towards medical card of Prudential Assurance Malaysia Berhad / Nor Mahirah Mustapha - Mustapha, Nor Mahirah (Faculty of Business and Management, 2010)
The purpose of this study is to evaluate the awareness and behaviours of Malay ethnic towards promotional tools, branding, and also services effort in the purchase of medical card by Prudential Assurance Malaysia Berhad. Awareness can be identifying as the state or ability to perceive, to feel, or to be conscious of events, objects or sensory patterns. More broadly, it is the state or quality of being aware of something. In biological psychology, awareness is defined as a human's perception and cognitive reaction to a condition or event, As we know, PRU health which is the brand of medical card by Prudential is a plan that provides comprehensive medical coverage by reimbursing major medical expenses incurred in the event of hospitalization, surgery or outpatient treatment. Because of that, medical card of Prudential plays the major roles in human life. In this study, it will discuss one of the important area within promotion tools, branding, and services effort as the marketing activities that can give impacts in evaluating overall customer feedback performance especially awareness towards the importance of medical card by Prudential. These elements have its own sub sector that describe different approach in determining the impacts the customer awareness as well as the potential clients of this medical card. This study will take the Prudential Assurance Malaysia Berhad, a most quality insurance company in Malaysia will stress more on specific area that can influence people to buy medical card as fast as possible. Most of the customers have affected by specific environment during the process of information delivery. The attributes that give impacts on customer awareness are promotion tools, branding, and also services effort. There are lots of suggestions from this study and might be useful for future improvement for Prudential it.